Developmental regulation of genes encoding Universal stress proteins in Schistosoma mansoni (2011)
The draft nuclear genome sequence of the snail-transmitted, dimorphic, parasitic, platyhelminth Schistosoma mansoni revealed eight genes encoding proteins that contain the Universal Stress Protein (USP) domain. Schistosoma mansoni is a causative agent of human schistosomiasis, a severe and debilitating Neglected Tropical Disease (NTD) of poverty, which is endemic in at least 76 countries. The availability of the genome sequences of Schistosoma species presents opportunities for bioinformatics and genomics analyses of associated gene families that could be targets for understanding schistosomiasis ecology, intervention, prevention and control. Proteins with the USP domain are known to provide bacteria, archaea, fungi, protists and plants with the ability to respond to diverse environmental stresses. In this research investigation, the functional annotations of the USP genes and predicted nucleotide and protein sequences were initially verified. Subsequently, sequence clusters and distinctive features of the sequences were determined. A total of twelve ligand binding sites were predicted based on alignment to the ATP-binding universal stress protein from Methanocaldococcus jannaschii. In addition, six USP sequences showed the presence of ATP-binding motif residues indicating that they may be regulated by ATP. Public domain gene.